2018
DOI: 10.29322/ijsrp.8.8.2018.p8030
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Methodology For optimisation of hot air drying of water yam slices

Abstract: Response surface methodology was used to investigate the effects of temperature, thickness and time on the drying of water yam slices and to determine the optimised condition for hot air drying. The predominant falling rate drying regime was observed. Experiments were performed at air temperature of 60 o C, 70 o C and 80 o C, slice thickness of 4, 6 and 8mm and drying times of 60, 165 and 270minutes. Based on response surface and desirability functions, the optimum conditions for water yam drying were: air tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
0
0
Order By: Relevance
“…It was also found that as the drying temperature increased, the ratio of moisture of sweet potato slices decreased with reduced slice thickness. The observation is in accordance with earlier reports (Aneke et al, 2018; Sobowale et al, 2020).…”
Section: Resultssupporting
confidence: 94%
“…It was also found that as the drying temperature increased, the ratio of moisture of sweet potato slices decreased with reduced slice thickness. The observation is in accordance with earlier reports (Aneke et al, 2018; Sobowale et al, 2020).…”
Section: Resultssupporting
confidence: 94%
“…EU and EUR had an adequate precision higher than 4, representing sufficient discrimination of the models. Adequate precision evaluates the signal to the ratio of noise that is reasonably higher than 4 [47]. The values of adequate precision for EU and EUR were 28.75 and 41.64, respectively, while the values of PRESS for the selective model were found to be 0.0038 and 0.0078, respectively (Table 6).…”
Section: Experimental Uncertaintymentioning
confidence: 96%
“…The values of adequate precision for EU and EUR were 28.75 and 41.64, respectively, while the values of PRESS for the selective model were found to be 0.0038 and 0.0078, respectively (Table 6). The ratios of 28.75 and 41.64 for EU and EUR represented an adequate signal, so these models could be utilised to navigate the space of design [47]. Through the utilisation of multiple regression assessment on the drying experimental data, the following quadratic polynomial equations were found to indicate energy utilisation and energy utilisation ratio:…”
Section: Experimental Uncertaintymentioning
confidence: 99%